Displacement damage effects induced by fast neutron in backside-illuminated CMOS image sensors. Issue 9 (1st September 2020) - Zhang, Xiang; Li, Yudong; Wen, Lin; Feng, Jie; Zhou, Dong; Cai, Yulong; Liu, Bingkai; Fu, Jing; Guo, Qi
ABSTRACT: BackSide-Illuminated (BSI) CMOS Image Sensors (CISs), with developed performance on quantum efficiency and sensitivity, have been applied for aerospace missions and gradually replaced FrontSide-Illuminated (FSI) CISs. Two types of BSI CISs with different epitaxial layer thicknesses were irradiated by 14-MeV neutron up to 3.40 × 10 11 n/cm 2 to analyze the degradation induced by neutron irradiation. Dark current, dark current distribution, full well capacity, and spectral response were tested before and after the neutron irradiation and at different annealing time points with various temperatures. The results were analyzed to characterize the degradation introduced by the unique backside passivation layer, and the converse illuminated direction. The interface states induced by displacement damage effects at the backside passivation layer were considered as a novel origin of dark current which was not involved in FSI CISs.